Studi Komparasi Pengajaran Yoga Di Athaya Studio Dan Unit Kegiatan Mahasiswa Yoga Institut Hindu Dharma Negeri Denpasar - Komang Agustyana Putra; I Nyoman Linggih; Ni Putu Winanti (Kamaya: Jurnal Ilmu Agama, 2018)
Based on the phenomenon of variations or differences in the teaching of yoga in the community, especially at Athaya Studio and Student Activity Unit of Yoga Institute of Hindu Dharma Negeri Denpasar. So the author is interested to examine the teaching of yoga by trying to find similarities and differences. On the basis of this research is focused on Comparative Study of Yoga Teaching at Athaya Studio and Student Activity Unit of Yoga Institute of Hindu Dharma Negeri Denpasar. This research raises three problems: 1) The process of teaching yoga at Athaya Studio and Student Activity Unit of Yoga Institute of Hindu Dharma Negeri Denpasar; 2) Yoga teaching function at Athaya Studio and Student Activity Unit of Yoga Institute of Hindu Dharma Negeri Denpasar; and 3) Yoga teaching stages at Athaya Studio and Student Activity Unit of Yoga Institute of Hindu Dharma Negeri Denpasar. The objectives of this research are: 1) To know the process of teaching yoga at Athaya Studio and Student Activity Unit of Yoga Institute of Hindu Dharma Negeri Denpasar, 2) To know the teaching function of yoga at Athaya Studio and Student Activity Unit of Yoga Institute Hindu Dharma Negeri Denpasar , and 3) To know the stages of yoga teaching at Athaya Studio and Student Activity Unit of Yoga Institute of Hindu Dharma Negeri Denpasar. To achieve this objective, this research uses the theoretical basis to dissect the problem. The theory to be used is Structural Functional Theory, and Behaviorism Theory. The process of teaching yoga at Athaya Studio and the Student Activity Unit of Yoga Institute of Hindu Dharma Negeri Denpasar has a different number of teaching methods used. Yoga teaching function there are similarities that work to improve health, self-control, and improve the spiritual. Stages in yoga teaching there are also similarities, the stage consists of four phases of preparation phase, preliminary phase, core phase, and closing phase.